Development of Web Programming Interactive Learning Multimedia in Vocational Middle School - Alfikri Alam; Indri Astuti; Dede Suratman (JTP - Jurnal Teknologi Pendidikan, 2022)
The research aimed to develop interactive multimedia learning on web programming materials in Vocational High schools. This research was conducted at SMK Negeri 1 Sajingan Besar, with the research subjects were students in class XI of Software Engineering expertise competency as many as 48 students. The research method used is a 4D model consisting of four stages, namely define stage, design, develop, and disseminate. Interactive learning multimedia developed validated by three media experts with an average result of 3.9 with a category of "valid," 3 material experts with an average result of 4.09 with a category of "very valid" and three design experts with an average score of 4.32 with a category of "very valid." Developer trials with an average value of 82.9% with "positive" criteria. Multimedia has an initial view that contains several menus, namely material, SK-KD, Quiz, Help, About, and Download. The effectiveness of the use of interactive learning multimedia is done by looking at the responses of students and learning outcomes. The response result of 48 students was with an average score of 81.91% with the criteria "positive." The average student learning outcome for pre-test was 37.33 and for post-test was 59.97, with a difference of 22.64. Based on the results of the T-test that the sig value (2-tailed) is 0.000 < 0.05 and the t value counts > t table, (23,778) > (2.35), These results show there is a significant difference between before and after using interactive learning multimedia on web programming materials. As for the effect size test was conducted to find out the level of effectiveness in the use of interactive learning multimedia with a value of 2.83 with the category "Strong Effect."